Avaliação e seleção de rizobactérias associadas a Paspalum vaginatum para desenvolvimento de novos bioinsumos - Lisboa, Paulo Henrique Gomes (Universidade Federal de São Carlos, 2024)
Embrapa Southeast Livestock holds the second-largest germplasm bank of Paspalum in the world, including Paspalum vaginatum, a coastal plant resistant to saline and waterlogged soils, used for erosion control and sports lawns and P. regnellii, a highly nutritious grass with potential use as forage. Research in the US turfgrass industry has received investments, but its environmental and productive impacts are still uncertain. In the Brazilian market, Paspalum sp. has been attracting attention; however, there are still few grass producers of this genus. These industries benefit from applying P. vaginatum since it has high salt tolerance and is a dense grass with an intense color, making it ideal for landscaping and sports fields in coastal areas. Plant growth-promoting rhizobacteria (PGPR) can sustainably increase productivity by improving nutrient availability and aiding in plant establishment. The formulation of bioinputs can ensure the sustainability of production systems and Brazil's autonomy with agroecological technologies. This work aims to characterize and identify 145 rhizosphere bacteria from P. vaginatum, evaluating their in vitro potential for biological nitrogen fixation (BNF) (18 % of isolates), phosphate solubilization (PS) (18.6 %), indolic compounds production (0.09 to 57.38 ug.mL-1), and antagonism to phytopathogenic fungi Bipolaris sp. and Colletotrichum sp. which cause leaf spot and anthracnose diseases in Paspalum species, respectively. Eight isolates showed antagonistic capacity against both phytopathogenic fungi. Five promising isolates in the in vitro BNF and PSI assays, also indolic compounds producers, were selected for plant growth promotion in P. vaginatum in a greenhouse, using the bioinoculant BiomaPhos® as a positive control. The identified rhizobacteria belong to various genera, including Actinomycetia, Agrobacterium, Amycolatopsis, Bacillus, Burkholderia, Dyella, Enterobacter, Kitasatospora, Paenibacillus, Priestia, Pseudomonas, Rhizobium, Streptomyces, among others. The inoculation of the five selected isolates in P. vaginatum resulted in average root dry biomass statistically similar to the commercial inoculant BiomaPhos and the control, with no harmful effects. In Brazil, it is currently estimated that 32.5 thousand hectares of the territory are dedicated to grass production. Simultaneously, the sustainability of pastures, essential for Brazilian livestock, requires proper management and phosphorus fertilization, usually using expensive superphosphates or gradually releasing natural phosphates. Superphosphates have high agronomic efficiency but raise future sustainability concerns. Therefore, exploring the combined use of phosphate fertilizers with phosphate-solubilizing bacteria is a path to consider. This study also investigated rhizobacteria associated with P. vaginatum associated with P. vaginatum in the initial development and control of anthracnose in another species of the genus, P. regnellii, which has high forage potential. Five rhizospheric isolates were tested in vivo for growth promotion by increasing dry biomass in P. regnellii, using BiomaPhos® as a positive control, and subjected to in vitro soluble P quantification. Bacteria selected based on in vitro phosphate solubilization quantification were subjected to an initial establishment assay in P. regnellii in a greenhouse, in soil fertilized with triple superphosphate, Araxá rock and Bayovar rock, as well as the control (unfertilized soil). Isolates with antagonistic activity were selected for biocontrol tests against Colletotrichum sp., the etiological agent of anthracnose in P. regnellii and in a greenhouse. Rhizobacteria associated with P. vaginatum showed a positive effect on germination and establishment of P. regnellii when combined with soil corrected with lime and fertilized with triple superphosphate and in limed, unfertilized soil, highlighting isolate 5 (Acinetobacter sp.). Isolate 111 (Amycolatopsis sp.) significantly reduced the intensity of anthracnose caused by Colletotrichum sp. in P. regnellii.
Evaluation and selection of rhizobacteria associated with Paspalum vaginatum for the development of new bioinputs
Keywords: Paspalum; RPCV; Biocontrole; Paspalum; PGPR; Biocontrol; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::BIOLOGIA E FISIOLOGIA DOS MICROORGANISMOS::BACTEROLOGIA; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MICROBIOLOGIA E BIOQUIMICA DO SOLO; CIENCIAS BIOLOGICAS::MICROBIOLOGIA; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA APLICADA